1976
DOI: 10.1039/c39760001061
|View full text |Cite
|
Sign up to set email alerts
|

Formation of organonitrogen compounds via neutral ruthenium nitrosyl complexes

Abstract: THE formation of N-C bonds via the intermediacy of ruthenium nitrosyl complexes has been described in two instances : (i) the reaction of [Ru (bipyridyl),(NO) XI,+ (X = C1 or NO,) with 'activated' arylamines,l e.g. PhNMe,, when Ru-co-ordinated p-Me,NC,H,NO is formed, and (ii) the radiolysis of [Ru(NH,),(N0)l3+ in solutions containing. ButOH,, when metal-bound Me,C(CH,NO) (OH) is produced. However, by virtue of the use of charged ruthenium nitrosy1 (Received, 29th October 1976; Corn. 1209.) 7 PhCH,Br was chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The ruthenium complex [ Ru( CO) 2(NNPh)(PPh3)2] [PFs] (11) shows somewhat different behavior. The deprotonated complexes will slowly extract protons from freshly distilled methanol or ethanol; thus, the freshly prepared complexes must be rapidly filtered and removed from the reaction solvent since it contains small amounts of methanol or water.…”
Section: Discussionmentioning
confidence: 99%
“…The ruthenium complex [ Ru( CO) 2(NNPh)(PPh3)2] [PFs] (11) shows somewhat different behavior. The deprotonated complexes will slowly extract protons from freshly distilled methanol or ethanol; thus, the freshly prepared complexes must be rapidly filtered and removed from the reaction solvent since it contains small amounts of methanol or water.…”
Section: Discussionmentioning
confidence: 99%
“…Although mechanistic studies have not been reported, it is suggested that the reaction proceeds via oxidative addition of benzyl halide to be cobaltate anion: "o=n; In a more recent study, the reactions of benzyl bromide with neutral nitrosyl complexes in hydrocarbon solvents have been examined. 78 Benzyl bromide is a particularly convenient substrate, since, if it is converted to PhCH2NO, it will readily tautomerize to PhCH=NOH, which is easily characterized. The most extensively investigated compound has been [Ru(NO)2-(PPh3)2], which is relatively stable In solution and is easily prepared.…”
Section: Formation Of N-c Bondsmentioning
confidence: 99%
“…The proposed formulation was confirmed by fortuitously obtained by reaction of [Re(CO) 4 Cl] 2 with an X-ray diffraction study (see later). K[HB(dmpz) 3 ] [12] .…”
Section: Introductionmentioning
confidence: 99%